Maximal Cohen–Macaulay modules over certain Segre products. Issue 6 (3rd June 2019) - Ma, Linquan
Abstract: We prove some results on the non-existence of rank one maximal Cohen–Macaulay modules over certain Segre product rings. As an application we show that over these Segre product rings there do not exist maximal Cohen–Macaulay modules with multiplicity less than or equal to the parameter degree of the ring. This disproves a conjecture of Schoutens [14 ].